2017
DOI: 10.1007/s10461-017-1850-2
|View full text |Cite
|
Sign up to set email alerts
|

Injection Drug Use, Unemployment, and Severe Food Insecurity Among HIV-HCV Co-Infected Individuals: A Mediation Analysis

Abstract: Severe food insecurity (FI), which indicates reduced food intake, is common among HIV-hepatitis C virus (HCV) co-infected individuals. Given the importance of unemployment as a proximal risk factor for FI, this mediation analysis examines a potential mechanism through which injection drug use (IDU) is associated with severe FI. We used biannual data from the Canadian Co-infection Cohort (N = 429 with 3 study visits, 2012-2015). IDU in the past 6 months (exposure) and current unemployment (mediator) were self-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Given the prevalence of deaths related to drug poisoning in our sample (results not shown), our finding on unintentional injuries may partly reflect the link between food insecurity and substance use, 49,50 which is often complicated by the coexistence of HIV infec tion and depression. [51][52][53] The higher risk of death from suicides is consistent with Canadian studies documenting links between food insecurity and suicidal ideation and attempts. [19][20][21] Suicide preven tion needs to be prioritized for adults experiencing food insecurity.…”
Section: Discussionsupporting
confidence: 82%
“…Given the prevalence of deaths related to drug poisoning in our sample (results not shown), our finding on unintentional injuries may partly reflect the link between food insecurity and substance use, 49,50 which is often complicated by the coexistence of HIV infec tion and depression. [51][52][53] The higher risk of death from suicides is consistent with Canadian studies documenting links between food insecurity and suicidal ideation and attempts. [19][20][21] Suicide preven tion needs to be prioritized for adults experiencing food insecurity.…”
Section: Discussionsupporting
confidence: 82%
“…However, even in the absence of repeated measurements on participants, regression analyses typically generate more meaningful estimates if there is at least a hypothesized temporality of the relationships under examination (3,4,7) . In our papers, we concluded that a hypothetical intervention on IDU may potentially reduce FI (10,11) . While this conclusion was contingent upon several assumptions (e.g.…”
mentioning
confidence: 87%
“…After an examination of the relevant literature (13) , we decided to focus our attention on IDU as an exposure variable and FI as a potential consequence of this behaviour. We conceptualized this analysis (10) , in time, using a directed acyclic graph, which is a visual representation of the hypothetical relationship between variables (7,14) . Unlike the cross-sectional study by Patil et al (8) , we benefited from the use longitudinal cohort data, which allowed us to temporally order the exposure (IDU) and outcome (FI) measures in our data set through variable lagging (10,11) .…”
mentioning
confidence: 99%
See 2 more Smart Citations